Eigenvalue Problem with Moving Discontinuity Points - Hira, Fatma; Altinisik, Nihat (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we present a Sturm Liouville problem which has discontinuities in the neighborhood of the midpoint of an interval. Also the problem contains an eigenparameter in one of the boundary conditions. We derive operator theoretic formulation in suitable Hilbert space, give some properties of the eigenvalues and obtain asymptotic formulas for the eigenvalues and the corresponding eigenfunctions.